Decalcifying capability of irrigating solutions on root canal dentin mineral content - Claudio Poggio; Alberto Dagna; Andrea Vinci; Riccardo Beltrami; Lucia Cucca; Luciano Giardino (Wolters Kluwer Medknow Publications, 2015)
Background: Chelating agents are believed to aid root canal irrigation and to be able to remove the inorganic smear layer. Aims: The purpose of the present study was to evaluate and to compare the decalcifying capability of different irrigating solutions (Tubuliclean, Largal Ultra, ethylenediaminetetraacetic acid 17%, Tetraclean, Tetraclean NA). Materials and Methods: Sixty maxillary central incisors were used. Root canals were instrumented and irrigated. From each root, four comparable slices of cervical dentin were obtained. At three successive 5-min interval immersion times, the concentration of calcium extracted from root canal dentin was assessed with an inductively coupled plasma-atomic emission spectrometer. Statistical Analysis Used: Data were analyzed by means of Kruskal Wallis and Mann-Whitney tests. Significance was predetermined at P < 0.05. Results and Conclusions: For all irrigating solutions, the maximum amount of Ca 2+ extracted from root canal dentin samples was reached after 10 min contact time except for citric acid-based agents (Tetraclean and Tetraclean NA) which induced a higher and still increasing calcium release even after 10 min contact time. In order to obtain an efficient decalcifying action on dentin and to facilitate the biomechanical procedures, citric acid-based irrigants can be applied.